2013
DOI: 10.20870/oeno-one.2013.47.4.1559
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the efficiency of some of the most usual DNA extraction methods for woody plants in different tissues of <em>Vitis vinifera</em> L.

Abstract: <p style="text-align: justify;"><strong>Aim</strong>: To compare different methods for extracting DNA from non-recalcitrant and recalcitrant tissues of <em>Vitis vinifera</em> woody plants and propose a modification of a previously published method to reduce the time and cost of extraction.</p><p style="text-align: justify;"><strong>Methods and results</strong>: DNA was extracted from young and mature leaves as well as from stems and seeds using some of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
(113 reference statements)
2
13
0
Order By: Relevance
“…This suggested that this DNA extraction protocol is effective to isolated DNA from matured and young leave. Similar result was also described by Marsal et al (2013) based on their studies on woody plants. Similarly, Marsal et al (2011) reported that young and matured leave provide good result than the recalcitrant tissues (seeds and stems).…”
Section: Genomic Dna Yieldsupporting
confidence: 90%
See 3 more Smart Citations
“…This suggested that this DNA extraction protocol is effective to isolated DNA from matured and young leave. Similar result was also described by Marsal et al (2013) based on their studies on woody plants. Similarly, Marsal et al (2011) reported that young and matured leave provide good result than the recalcitrant tissues (seeds and stems).…”
Section: Genomic Dna Yieldsupporting
confidence: 90%
“…However, the DNA contaminants have varied along with plant tissue type and even along with the different species (Lucas et al, 2019). Many studies are carried out for plant DNA extraction either to optimize the DNA extraction protocol or to select best plant tissue for quality DNA extraction (Hasan et al, 2012;Marsal et al, 2013). But optimizing DNA extraction protocol…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA was extracted using the method described by Marsal et al (2013) (based on Fort et al (2008) and Marsal et al (2011) protocols). The grapevine genepool was genotyped at 20 SSR markers, which were selected for their capacity for discrimination and polymorphism in agreement with previous studies: VVS2, VVS3, VVS29 (Thomas and Scott, 1993); VVMD5, VVMD6, VVMD7 (Bowers et al, 1996); VVMD27, VVMD28, VVMD36 (Bowers et al, 1999b); VrZAG21, VrZAG47, VrZAG62, VrZAG64, VrZAG79, VrZAG83 (Sefc et al, 1999); scu06vv (Scott et al, 2000); VvUCH11, VvUCH12, VvUCH19 (Lefort et al, 2002); VChr19a (Cipriani et al, 2010).…”
Section: Microsatellite Genotypingmentioning
confidence: 99%